Modelling reactive power support from a generic wind power plant - Ågren,Matti (CODEN:LUTEDX/TEIE, 2025)
As the amount of wind power in electricity production increases it becomes more important that they are able to provide ancillary services to support power system stability. This thesis investigates how a generic wind power plant can provide reactive power for voltage support. To represent a generic wind power plant, the Western Electricity Coordinating Council’s generic Renewable Energy System models are parametrised using only open source data. For different parameter choices in the reactive power control path, short term voltage stability is evaluated, by studying the voltage recovery following a 3-phase short circuit. A distribution system is modelled with four types of induction motors as well as an electronic and static load. This dynamic load is parametrised using a statistics based approach of the average energy consumption in Sweden. The wind power models are analysed at different model complexity, as a single wind turbine, a wind power plant and as a part of a large network. It is found that the parameters that are hardest to determine with only open sources, are also the ones that least affect the reactive power support from a short term voltage stability perspective. The wind power plant model can provide better reactive power support than a standard synchronous generator model and the presence of a wind power plant is able to prevent a voltage collapse and rotor angle instability. An identified challenge is that for wind power penetration levels above 15 % (33 % locally), decreased network strength can cause unstable voltage oscillations to arise. These oscillations are affected by the parametrisation of the wind power models.
Keywords: generic wind power models; inverter based resources; reactive power support; short term voltage stability; induction motors; network strength; short circuit ratio